Alloantigen specific deletion of primary human T cells by Fas ligand (CD95L)-transduced monocyte-derived killer-dendritic cells - Schütz, Christian (Blackwell Science Inc, 2011)
Numerous studies have been performed in vitro and in various animal models to modulate the interaction of dendritic cells (DC) and T cells by Fas (CD95/Apo-1) signalling to delete activated T cells via induction of activation-induced cell death (AICD). Previously, we could demonstrate that Fas ligand (FasL/CD95L)-expressing ‘killer-antigen-presenting cells’ can be generated from human monocyte-derived mature DC (mDC) using adenoviral gene transfer. To evaluate whether these FasL-expressing mDC (mDC-FasL) could eliminate alloreactive primary human T cells in vitro, co-culture experiments were performed. Proliferation of human T cells was markedly reduced in primary co-cultures with allogeneic mDC-FasL, whereas a strong proliferative T-cell response could be observed in co-cultures with enhanced green fluorescent protein-transduced mDC. Inhibition of T-cell proliferation was related to the transduction efficiency, and the numbers of mDC-FasL present in co-cultures. In addition, proliferation of pre-activated alloreactive CD4(+) and CD8(+) T cells could be almost completely inhibited in secondary co-cultures using mDC-FasL as stimulatory cells, which was the result of induction of apoptosis in the majority of preactivated T cells. The specific deletion of alloreactive T cells by mDC-FasL was confirmed by an unaffected proliferative response of surviving T cells towards allogeneic ‘third-party’ peripheral blood mononuclear cells in a third stimulation, or upon unspecific stimulation with anti-CD3/CD28 beads. The results of this study demonstrate that allospecifically activated T cells are efficiently eliminated by mDC-FasL, supporting further investigations to apply FasL-expressing ‘killer-DC’ as a novel strategy for the treatment of allograft rejection.